Подведение итогов - Жаравин Анатолий Иванович (Удмуртия, 2008)
Экземпляры: ЦБ (20171211) / Инвентарный номер: 49662 / Цена: 40.00 / Сис.шифр: 84(2Рос=Удм) / Авт.знак: Ж 34 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)